An Empirical Study of the Effect of Tax Planning and Leverage on Company Value: Studi Empiris Pengaruh Tax Planning Dan Leverage Terhadap Nilai Perusahaan - Roin Nur Rohmah; Untung Wahyudi; Khojanah Hasan; Muhammad Syafiq; Endah Puspitosarie (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
This study adopts a quantitative approach to evaluate the impact of tax planning on firm value, by examining tax avoidance, represented by the effective tax rate (ETR), and tax aggressiveness, measured by the book tax difference (BTD). This study also examines the leverage effect, proxied by the debt-to-equity ratio (DER), on firm value, measured by the price-to-book value (PBV) indicator, on 2020-2023 Indonesia Stock Exchange issuers listed. Observations includes 423 companies, selectively selected by purposive sampling technique. The secondary data used and obtained from annual financial reports available on the Indonesia Stock Exchange (IDX) official website. The data processing process was carried out using Eviews software version 13, which includes various stages of analysis such as descriptive statistics, model selection tests (the Chow test, the Hausman test, and the Lagrange multiplier test), to the final panel data regression hypothesis testing analysis, consisting of the r-square, the t, and the f-test. The research findings tax planning indicators, such as tax avoidance and tax aggressiveness, partially do not have a significant impact on company value. In contrast, leverage is statistically proven to have a significant impact on company value. However, when all three variables are tested simultaneously, the results indicate a significant influence on overall company value. It is recommended that companies integrate tax planning and leverage strategies into long-term financial planning and communicate these financial policies transparently to stakeholders, including investors, through annual reports and public exposures. This step aims to increase market confidence and company value in a sustainable manner.